2013
DOI: 10.1111/1567-1364.12111
|View full text |Cite
|
Sign up to set email alerts
|

Not your ordinary yeast: non-Saccharomycesyeasts in wine production uncovered

Abstract: Saccharomyces cerevisiae and grape juice are 'natural companions' and make a happy wine marriage. However, this relationship can be enriched by allowing 'wild' non-Saccharomyces yeast to participate in a sequential manner in the early phases of grape must fermentation. However, such a triangular relationship is complex and can only be taken to 'the next level' if there are no spoilage yeast present and if the 'wine yeast' - S. cerevisiae - is able to exert its dominance in time to successfully complete the alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
700
1
21

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 720 publications
(743 citation statements)
references
References 188 publications
(279 reference statements)
21
700
1
21
Order By: Relevance
“…Other authors have reported higher glycerol production for other non-Saccharomyces species (Comitini et al, 2011;Gobbi et al, 2013). Although other yeast species such as Candida stellata have been described as higher producers of glycerol up to 14 g/L (Jolly et al, 2014), the use of Schizosaccharomyces to improve this quality parameter could be interesting.…”
Section: Glycerolmentioning
confidence: 98%
See 1 more Smart Citation
“…Other authors have reported higher glycerol production for other non-Saccharomyces species (Comitini et al, 2011;Gobbi et al, 2013). Although other yeast species such as Candida stellata have been described as higher producers of glycerol up to 14 g/L (Jolly et al, 2014), the use of Schizosaccharomyces to improve this quality parameter could be interesting.…”
Section: Glycerolmentioning
confidence: 98%
“…The world wine market is experiencing increasing interest in new yeast strains that can produce unique wines with novel properties (Benito et al, 2015a;Carrau et al, 2015;Englezos et al, 2015;Esteve-Zarzoso et al, 1998;Fleet, 2008;Jolly et al, 2014Jolly et al, , 2006Medina et al, 2013;Pretorius, 2000;Uthurry et al, 2004). This is the reason that certain non-Saccharomyces yeast, such as Schizosaccharomyces, which have the ability to lower the malic acid content of wine, could prove to be an excellent alternative to lactic acid bacteria and are currently viewed with much interest (Benito et al, 2015b(Benito et al, , 2014aFleet, 1999;Suárez-Lepe et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is also well know that the development of some non-Saccharomyces yeast such as Torulaspora delbrueckii during alcoholic fermentation can improve wine quality as well as their complexity [8,9]. Recently, our research group has proposed the use of T. delbrueckii as a tool for improving the foam properties in sparkling wine production [10].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows that, according to several population studies on grape and must microbiome [4,15,31], Hanseniaspora uvarum was the most abundant nonSaccharomyces yeast found in must, being around a 50% of the total. Its low fermentative power causes the rapid decrease of H. uvarum during the early stages of wine fermentation, so besides its low production of hydrolytic enzymes, its influence on final wine composition is not significant.…”
Section: Population Study Rational Use Of Genomic Technologymentioning
confidence: 99%
“…Enzymatic properties of different microorganisms involved in winemaking process (bacteria and yeasts, mainly) have been studied for a long time [1], but yeasts have featured this applied research line as the main microorganism responsible of the alcoholic fermentation process [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%